Subcutaneous Heparin Therapy during Pregnancy: a Need for Concern at the Time of Delivery - Anderson, David R; Ginsberg, Jeffrey S; Burrows, Robert; Brill-Edwards, Pat (Thrombosis and Haemostasis, 1991)
Subcutaneous heparin is the treatment of choice for women requiring anticoagulant therapy during pregnancy. However, heparin therapy presents a management problem at delivery because of its potential to cause a persistent anticoagulant effect and thus increase the risk of bleeding. In order to avoid therapeutic complications it has been our practice to have women eithei discontinue their heparin injections with the onset of labour or to terminate heparin injections 12 h prior to elective induction. To determine the safety of our anticoagulant protocol at delivery we reviewed consecutive patients treated with subcutaneous heparin therapy during pregnarcl, at our centre. Over a 23 month period we found that six of 11 women receiving subcutaneous heparin during pregnancy delivered while their aPTT was prolonged. In addition, three women received intravenous protamine sulphate prior to delivery and in one patient major bleeding occurred during an emergency cesarean section. Those women who had elevated aPTTs at the time of delivery all gave birth within 28 h of their last injection of heparin. In order to avoid a prolonged aPTT at delivery, we have now adopted a more conservative approach to the management of subcutaneous heparin use at term. Subcutaneous heparin is discontinued 24 h prior to commencing an elective induction of labour.